(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Bacground: Amoebiasis is a protazon infection of the human intestine spread through the world the most prevelant form of the disease is amebic dysenterywhich characterizes acute diarrhoea with observable blood and mucus in stools. Aims: This article aimed to detects the role of IL-25 and IL-35 in the immune response against amebic dysentery. Methods: This study was conducted in Thi-Qar province-Al-Nasiriyah city in Muhammad Al-Mousawi Hospital for Children, the study included collection of (60)blood samples from amebiasis patients and (30) apparently healthy children at a period from September 2019 to March 2020 with the age less than one year to 15 years that divides to four age groups, the levels of IL-25 and IL-35 were determined by ELISA technique. Results:The results indicate that the IL-25 and IL-35 concentrations in serum samples from amoebiasis patients were significantly higher when compared with that from healthy controls. The highest level of IL-25 was recordsin the third age group of patients with level 1677.2 ± 867.2ng /ml,compare with the high level in the third age group of control with level 450.40 ± 97.31ng /ml.Also, the findings indicates the highest level of IL-35 records35 in the second age group of patients with level 291.0 ± 62.3ng /ml, while the high level recorded in the first age group of control with level 8.246± 0.60 ng /ml.